O método da iteração inversa com deslocamento aplicado ao operador de Sturm-Liouville - Mario Daniel Huamán Bolaños (2013)
In this work we use an iterative method inspired by the inverse iteration with shift technique of linear linear algebra to find the eigenvalues and eigenfunctions of the Sturm-Liouville problem. First, we set the function space where the operator is defined, emphasizing its relations with the classical and weak solutions of the problem, and later apply the iterative method to the Sturm-Liouville operator where our main interest will be thetheoretical study of the convergence of the method.